Overdiscrete echo‐planar spectroscopic imaging with correlated higher‐order phase correction. Issue 1 (11th December 2019) - Coello, Eduardo; Hafalir, Fatih S.; Noeske, Ralph; Menzel, Marion; Haase, Axel; Menze, Bjoern; Schulte, Rolf F.
Abstract : Purpose: To introduce a robust methodology for fast 1 H MRSI of the brain at 3T with improved SNR and reduced phase‐related artifacts. Method: An accelerated acquisition scheme using echo‐planar spectroscopic imaging (EPSI) was combined with the overdiscrete reconstruction framework. This approach enables the interleaved acquisition of a water reference scan at each phase encoding step, maximizing its correlation with the water‐suppressed measurement. Moreover, a generalized high‐order phase correction was incorporated into the reconstruction pipeline. The spatial–temporal phase correction term was estimated from the reference scan and interpolated to high resolution using a polynomial basis. The method was implemented at 3T and validated with phantom and in vivo experiments. Results: The methodology showed the elimination of spectral artifacts generated by phase disturbances and achieved mean SNR gains in vivo of 3.18 and 1.19 compared to standard reconstructions with corrections performed at nominal and high resolution, respectively. EPSI scans with interleaved water acquisition showed to be robust to system instabilities and potentially to patient motion. Moreover, phase distortions were effectively corrected in a single step, avoiding additional reference measurements and post‐processing steps. Conclusion: The overdiscrete reconstruction framework with high‐order phase correction allowed to effectively correct for distortions, related to B0 inhomogeneities, B0 drift, eddy currents, and system vibrations. Furthermore, the presented reconstruction method, combined with EPSI acquisitions, demonstrated improved measurement stability, substantial SNR enhancement, better spectral linewidth, and effective artifact removal.